Edukasi Sekolah Melalui Lomba Ular Tangga Pencegahan Stunting Kelompok Teman Sebaya - Lina Eta Safitri; Nurlaila Agustikawati; Putri Adekayanti (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Stunting is a condition of failure to thrive in children under five (babies under five years) resulting from chronic malnutrition so that children are too short for their age. Malnutrition occurs since the baby is in the womb and in the early days after the baby is born, however, stunting only appears after the baby is 2 years old. One of the causes of stunting is the lack of information about it. The purpose of this service is to create a learning atmosphere that is liked by children. The method used is counseling with snakes and ladders media. The result of this service is that elementary school students are happy when playing snakes and ladders games and become enthusiastic when studying